Transient Monocular Visual Loss Induced By Celecoxib: A Rare Adverse Effect - Norah Al-Harbi (Pakistan Journal of Medical & Health Sciences, 2022)
Background: The cyclooxygenase (COX) enzymes are competitively inhibited by nonsteroidal anti-inflammatory medications (NSAIDs). COX enzymes come in two distinct isoforms, each of which is encoded by a separate gene and has its own expression pattern. The therapeutic anti-inflammatory impact of NSAIDs is obtained by inhibiting COX-2 activity, whereas the majority of the unwanted side effects are caused by inhibiting COX-1 activity. As a result, selective COX-2 inhibitors are thought to have fewer negative effects. Medical disciplines such as rheumatology and orthopedics routinely prescribe COX-2 inhibitors like Celecoxib for the management and control of acute and chronic pain. Celecoxib is a medicine that is thought to be safe. Celecoxib, like other NSAIDs, can have side effects, the most prevalent of which are to the gastrointestinal (GI), cardiac, and renal systems. Ocular problems, which are included in the prescribing label as a potential concern, are among the less usually reported adverse effects of Celecoxib. Blurred vision, conjunctivitis, cataracts, and eye pain are among the side effects. More uncommon ocular problems have been recorded, including acute temporary and even severe permanent vision impairment. To my knowledge, this is the first published study on Celecoxib-related monocular vision loss.